Managing Public Relations ; Using Radio for Primary Health Care - Robert E. Myers Jr.; James W. King (Journal of Applied Communications, 1984)
Reviews of Managing Public Relations, by James E. Grunig and Todd Hunt; Using Radio for Primary Health Care, by W. A. Sweeney and M. B. Parlato.